Qualitative Research to Enhance the Evaluation of Results-Based Financing Programmes : The Promise and the Reality - Cataldo, Fabian; Kielmann, Karina (World Bank, Washington, DC, 2016)
This Discussion Paper presents the approach, findings, and recommendations from a desk review of the qualitative research conducted within Results-Based Financing programmes (RBF) under the Health Results Innovations Trust Fund (HRITF). The review included 17 studies conducted in Benin, Burundi, Cameroon, DRC, Ethiopia, Haiti, Kenya, Kyrgyzstan, Nigeria, Rwanda, Tajikistan, Tanzania, Zambia, and Zimbabwe. The studies reveal a body of high quality work that is consistent with the conceptual framework of RBF schemes, supported by political will, resources, and research capacity. Strengthening the added value of qualitative inquiry in on-going and future qualitative studies may be enabled by small shifts in thinking and practice, in line with a qualitative research paradigm. First, in order to better ground research in an existing country and system specific context, some interrogation of constructs and posited relationships in the existing conceptual framework for intervention/evaluation may be required. Second, to enable more in-depth and richer data that documents working practices and relations under RBF schemes, training of local researchers should place stronger emphasis on entry to the field, gaining trust, building rapport, and sustaining a dialogue with key informants. Third, smaller, more intensive and focused studies targeting fewer sites and smaller samples - but addressing a wider range of methods and informants within the health system - are likely to yield richer data that can support the understanding of how health workers and managers are responding to schemes, and what impact schemes have on service volumes and outputs.